2019
DOI: 10.1002/app.47691
|View full text |Cite
|
Sign up to set email alerts
|

IR spectroscopy: Suitable method for determination of curing degree and crosslinking type in melamine–formaldehyde resins

Abstract: Melamine–formaldehyde (MF) resins are widely used as adhesives and finishing materials in the wood industry. During resin cure, either methylene ether or methylene bridges are formed, leading to the formation of a three‐dimensional resin network. Not only the curing degree, but also the chemical species present in the cured resin determine the quality of the final product. Analytical methods allowing a detailed investigation of network formation are of great benefit to manufacturers. In the present work, resin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 39 publications
2
55
1
Order By: Relevance
“…The absorbance bands were assigned according to Weiss et al 42 The absorbance peak at 815 cm −1 is assigned to the triazine ring. All resin samples show the same intensity of the triazine vibration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorbance bands were assigned according to Weiss et al 42 The absorbance peak at 815 cm −1 is assigned to the triazine ring. All resin samples show the same intensity of the triazine vibration.…”
Section: Resultsmentioning
confidence: 99%
“…This explanation also agrees with DSC measurements of the commercially available MF pre‐condensate Kauramin® 773. Kauramin has a very low degree of pre‐condensation and with about 85 Jg −1 it has a significantly higher normalized total curing enthalpy H 42 …”
Section: Resultsmentioning
confidence: 99%
“…Chemical shifts at 14.75 ppm (δC b ) and 54.55 ppm (δC e ) were assigned to two carbons of ethoxyl group. The peak at 62.65 ppm (δC f ) was belonged to the carbon of methylol which reacted with aminopropyl group [CH 2 NH(CH 2 ) 3 ] . The 13 C NMR results indicated that the CH 2 NHCH 2  groups were generated by the methylol and aminopropyl groups.…”
Section: Resultsmentioning
confidence: 98%
“…Melamine, 2,4,6‐triamino‐1,3,5‐triazine, is a nitrogen‐rich organic compound and it has been widely used different applications such as textile, plastic, paint, flame retardant, paper coating, laminates, fertilizer, biosensor, and detection of heavy metal ions …”
Section: Introductionmentioning
confidence: 99%
“…19,20 Melamine, 2,4,6-triamino-1,3,5-triazine, is a nitrogen-rich organic compound 21 and it has been widely used different applications such as textile, plastic, paint, flame retardant, paper coating, laminates, fertilizer, biosensor, and detection of heavy metal ions. [22][23][24] In this work, biodegradable and antibacterial poly(azomethine-urethane) (PAMU)-and CS-based hydrogels have been fabricated by using CS for the controlled drug release application. Also, hydrophobicity, water uptake, in vitro biodegradation, protein absorption, antibacterial activity, and drug loading or release capacity have been evaluated to investigate the usability as biomaterials of the fabricated hydrogels.…”
Section: Introductionmentioning
confidence: 99%